AJARAN ETIKA POLITIK DALAM PAGELARAN WAYANG KULIT - Ariani, Iva (Yogyakarta, 2013)
Indonesia is an archipelagic country that has many culture inheritances. Traditional culture that liked by Indonesian people is a purwa leather puppet show.Purwa leather puppet show has many value in every part give many moral teachings that very valuable and important to human life in Indonesia, one of them is policial ethics education Purwa leather puppet show teach us how to love our country, be good citizen, and do human duty as citizen passes story that consist in it. Purwa leather puppet showalso contain philosophical that important to society. therefore purwa leather puppet show is very important if used to give political ethics education that appropriate to Indonesian character